Profiles of Higher Education Students Adopting Microlearning Strategies - Salas-Díaz, Fabiola; González-Bello, Edgar Oswaldo (Revista Electrónica Educare, 2023)
Introduction. Microlearning is the practice of using brief, fragmented, digital, and preferably mobile educational content for learning purposes. These elements coincide with young people’s practices regarding media consumption and digital resource usage. Various factors affect the adoption of microlearning, including the strategies that, as study actions, are adjusted to this practice. Objective. This research study aimed to analyze microlearning strategies to establish university students’ profiles and characterize them based on their technological affinity, motivation for learning objects, and perceived usefulness in educational platforms. Methodology. A quantitative approach was used with a non-experimental and cross-sectional design employing a digital questionnaire (n=1122). A k-means cluster analysis was applied. Results. Two groups of students were identified: “Favorable” (78%) and “Not Defined” (22%). The Favorable profile presented a higher level of technological affinity, perceived greater usefulness of educational platforms, and more motivation for learning matters. Students with favorable microlearning strategies viewed education with technology more positively and considered it essential to use technology in their lives. Working activity was a distinguishing characteristic of this group. Conclusions. It is concluded that university students presented heterogeneous actions to approach learning with technology. The majority of students (Favorable group) are more inclined towards technology usage and report actions consistent with microlearning, which supports the importance of promoting innovation in universities’ virtual spaces.